DINAMIKA IDENTITAS PROFESIONAL PEKERJA PADA ERA OTOMASI: ANALISIS NARATIF TERHADAP KARYAWAN SEKTOR MANUFAKTUR - Johan Maulana; Joko Prasetiyo; Mulyadi Mulyadi (Jurnal Manajemen & Pendidikan [JUMANDIK], 2026)
This study aims to examine in depth the dynamics of the professional identity of manufacturing sector employees in the face of an increasingly intensive wave of automation. Automation based on robotic technology and artificial intelligence has fundamentally changed the structure of work on the production floor, raising fundamental questions about how workers build, maintain, and change their professional identities in the midst of changes they cannot fully control. This study uses a Narrative Analysis approach that allows researchers to explore the construction of identity through the stories told by the participants themselves about their work life journeys. Data collection was conducted through in-depth narrative interviews with twelve employees working in the automotive and electronics manufacturing sector in the Central Java region who have experienced an automation transition in their workplaces for at least the past two years. Narrative analysis results in three main identity configurations, namely: identities that have collapsed and have not been reconstructed, identities that are in active negotiation, and identities that have been positively transformed. The findings of this study make an important contribution to the understanding of the psycho-social dimensions of technological disruption on the industrial workforce, as well as provide concrete implications for the design of worker empowerment and mentoring programs in the era of automation. Theoretically, this study enriches the conceptual framework of professional identity by including techno-social variables as determinants of identity dynamics that previously received less attention in the literature of vocational psychology and contemporary human resource management.